2014
DOI: 10.1121/1.4874356
|View full text |Cite
|
Sign up to set email alerts
|

Planar microphone based on piezoelectric electrospun poly(γ-benzyl-α,L-glutamate) nanofibers

Abstract: Velocity and pressure microphones composed of piezoelectric poly(γ-benzyl-α,L-glutamate) (PBLG) nanofibers were produced by adhering a single layer of PBLG film to a Mylar diaphragm. The device exhibited a sensitivity of −60 dBV/Pa in air, and both pressure and velocity response showed a broad frequency response that was primarily controlled by the stiffness of the supporting diaphragm. The pressure microphone response was ±3 dB between 200 Hz and 4 kHz when measured in a semi-anechoic chamber. Thermal stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, for a condensed microphone device, the output voltage from the device is frequency dependent. Normally, the cutoff frequency is greater than a few kHz for this type of the device . At a pressure of 30.8 kPa (40 N) with 1 Hz frequency, the generated V oc is ≈10 V, which is corresponding to a sensitivity of 325 mV kPa −1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, for a condensed microphone device, the output voltage from the device is frequency dependent. Normally, the cutoff frequency is greater than a few kHz for this type of the device . At a pressure of 30.8 kPa (40 N) with 1 Hz frequency, the generated V oc is ≈10 V, which is corresponding to a sensitivity of 325 mV kPa −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, many researchers have utilized a uniaxial stretching method to process PLLA film and show piezoelectricity along the shear direction of PLLA film . Recently, we reported that electrospun poly(γ‐benzyl‐α, L‐glutamate fibers can show piezoelectricity along the d 33 direction and can be used in microphone sensor applications . In this paper, we report for the first time that the electrospun PLLA nanofibers can show piezoelectricity along the fiber length direction (d 33 ) after electrospinning.…”
Section: Introductionmentioning
confidence: 87%